Penyuluhan kesehatan dan pelatihan pembuatan sabun dari minyak jelantah kepada santri dhuafa di Pesantren Tahfidzul Qur’an Kaffah Al-Mundzirin Palembang - Ahadito, Bijak Riyandi; Susilawati, Susilawati; Yuliasari, Nova; Yohandini, Heni; Hermansyah, Hermansyah (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2022)
Qur’an-Memorizing Boarding School Kaffah Al-Mundzirin Palembang is facing two problems: threat of scabies outbreak and poorly managed waste of used cooking oils. Production of soap from used cooking oil can be a two-pronged solution for these problems. Public Service Team from Faculty of Mathematics and Natural Sciences, Universitas Sriwijaya have carried out health counseling and training of soapmaking to 36 students, school administrators, and guests. Health counseling explains about the symptoms, spread, mitigation, and prevention of scabies, while soapmaking training explains about the cold process saponification method by demonstration. This activity has successfully implanted knowledge about scabies and method of soapmaking from used cooking oil within students and school administrators. Moving forward, we suggest that this activity to be accompanied with training of marketing methods and strategies so that the soap that were made can be turned into a sellable product to help with the school’s economy.